PENGARUH PEMBERIAN TANAH DAN SERBUK BAMBU TERHADAP BEBERAPA SIFAT KIMIA LIMBAH ORGANIK DAN ULTISOL LAMPUNG TENGAH - , SITI HIMAWATI; , Dr. Ir. Eko Hanudin, M. P. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
This research was aimed to know the effects of soil and bamboo addition on pH values, content of organic C, total N, total P, total K and total Mg and to know its effect of on chemical properties of Ultisols. This research was conducted in green house of Great Giant Pineapple Company since June to October 2013. This research was designed using Completely Randomized Design (CRD) with two factors, i.e soil addition (0%, 5%, 10% and 20%) and chopped bamboo addition (0% and 20%). Total of the treatments were eight with three replications. This research consisted of two experimental stage. The first stage was the composting of organic waste (cow manure 60%, cassava husk 20% and brommelain waste 20%) for one month and two months while the second stage was incubation of compost in Ultisols for one month. The result showed that soil addition could decrease of pH values, content of organic C, total N, total P, total K and total Mg. The addition of bamboo increased content of organic C, C/N ratio and content of total K and decreased content of total N. The compost incubation for one month did not give any significant effects on chemical properties of Ultisols.